Association of nail biting and psychiatric disorders in children and their parents in a psychiatrically referred sample of children - Ghanizadeh Ahmad (BMC, 2008)
Abstract Background Nail biting (NB) is a very common unwanted behavior. The majority of children are motivated to stop NB and have already tried to stop it, but are generally unsuccessful in doing so. It is a difficult behavior to modify or treat. The objective of this study was to investigate the prevalence of co-morbid psychiatric disorders in a clinical sample of children with NB who present at a child and adolescent mental healthcare outpatient clinic and the prevalence of psychiatric disorders in their parents. Method A consecutive sample of 450 referred children was examined for NB and 63 (14%) were found to have NB. The children and adolescents with nail biting and their parents were interviewed according to DSM-IV diagnostic criteria. They were also asked about lip biting, head banging, skin biting, and hair pulling behaviors. Results Nail biting is common amongst children and adolescents referred to a child and adolescent mental health clinic. The most common co-morbid psychiatric disorders in these children were attention deficit hyperactivity disorder (74.6%), oppositional defiant disorder (36%), separation anxiety disorder (20.6%), enuresis (15.6%), tic disorder (12.7%) and obsessive compulsive disorder (11.1%). The rates of major depressive disorder, mental retardation, and pervasive developmental disorder were 6.7%, 9.5%, 3.2%, respectively. There was no association between the age of onset of nail biting and the co-morbid psychiatric disorder. Severity and frequency of NB were not associated with any co-morbid psychiatric disorder. About 56.8% of the mothers and 45.9% of the fathers were suffering from at least one psychiatric disorder. The most common psychiatric disorder found in these parents was major depression. Conclusion Nail biting presents in a significant proportion of referrals to a mental healthcare clinic setting. Nail biting should be routinely looked for and asked for in the child and adolescent mental healthcare setting because it is common in a clinical population, easily visible in consultation and relatively unintrusive to ask about. If present, its detection can then be followed by looking for other more subtle stereotypic or self-mutilating behaviors.